A 3D printed smartphone adaptor for nasolaryngoscopy. Issue 1 (28th January 2020) - Thompson, Daniel; Albarki, Hashm; Lodhia, Chetan; Fitzpatrick, Nicholas
Abstract: Objective: The objective of this project is to create a three‐dimensional (3D) printed smartphone adaptor for flexible nasolaryngoscopy (FNL) to provide an affordable alternative to commercial options and a better fit than generic telescope phone adaptors. Method: We designed an adaptor using computer aided software to connect an iPhone XS to an Olympus Rhino‐Laryngo Fibre Scope. We experimented with various 3D printing materials and iterative designs to create a case that allowed for quality recording of a nasolaryngoscope exam using the iPhone's built in ×2 telescopic zoom lens. Results: Our 3D printed adaptor provides a cost‐effective alternative to commercially available FNL smartphone adaptors and is capable of capturing high‐quality images and videos of the nasopharynx and larynx. These images are useful for senior clinician review, decrease the need for repeat examination, can be utilized for education, avail telehealth review, and provides a way to digitally record examinations to electronic medical records for future comparison without the need for an endoscopy tower. Conclusion: Smartphone adaptors for FNL have been established to be of clinical value. Despite being simple devices, they continue to be expensive. This potentially limits access to junior clinicians, who stand to gain most from the ability to review images of examinations with senior colleagues. Our 3D printed smartphone case provides a cost‐effective alternative, with a better fit than generic adaptors, at a print cost of $29 AUD. This is $131 AUD less than the next cheapest commercial alternative. The files are freely available for use and modification. Level of Evidence: 4